Preparation and characterization of self-assembled chitosan nanoparticles for the sustained delivery of streptokinase: an in vivo study. (August 2014) - Modaresi, Seyed Mohamad Sadegh; Ejtemaei Mehr, Shahram; Faramarzi, Mohammad Ali; Esmaeilzadeh Gharehdaghi, Elina; Azarnia, Mahnaz; Modarressi, Mohammad Hossein; Baharifar, Hadi; Vaez, Seyed Javad; Amani, Amir
Abstract Chitosan (CS) nanoparticles have been extensively studied as carriers for therapeutic proteins in recent years. In this study, streptokinase loaded-CS nanoparticles were prepared and the pharmacokinetic parameters of streptokinase were compared with those of naked streptokinase. The preparation method included stirring the protein with the CS solution. The optimized combination was used for animal experiments to determine the streptokinase activity in rat plasma. Blood samples were collected at specified intervals and the activity assay was performed based on amidolysis activity of the chromogenic substrate, S2251, by streptokinase–plasminogen activator complex. The results demonstrated that streptokinase-loaded CS nanoparticles have more prolonged amidolytic activity in vivo compared to the naked one.